2021
DOI: 10.1039/d1tb01136g
|View full text |Cite
|
Sign up to set email alerts
|

A novel theranostic nanoplatform for imaging-guided chemo-photothermal therapy in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is highly malignant and invasive, and current treatments are limited due to serious side effects and unsatisfactory outcomes. Here, we reported the terbium ions-doped hydroxyapatite...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Although Doxo is not considered the gold standard for chemotherapy in OSCC, some studies have been reported the use of Doxo for noninvasive diagnostic imaging and therapeutical application using multifunctional nanotechnology to increase the intracellular uptake [ 13 , 14 ]. In tumor advancement, proto-oncogenes such as c-Myc and Bcl-2 are considered as genes that regulate cellular proliferation and apoptosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Doxo is not considered the gold standard for chemotherapy in OSCC, some studies have been reported the use of Doxo for noninvasive diagnostic imaging and therapeutical application using multifunctional nanotechnology to increase the intracellular uptake [ 13 , 14 ]. In tumor advancement, proto-oncogenes such as c-Myc and Bcl-2 are considered as genes that regulate cellular proliferation and apoptosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gu et al reported that terbium ion-doped hydroxyapatite (HATb) nanoparticles can be used as luminescent probes to encapsulate the NIR photothermal agent PDA and DOX for imaging guided synergistic therapy of chemotherapy and PTT [ 3 ]. Xu et al successfully prepared a new nanosystem for OSCC using HA and hollow mesoporous Prussian blue nanoparticles, which were loaded with DOX (HMPBs&DOX@HAMNs).…”
Section: Organic Nanoparticlesmentioning
confidence: 99%
“…For centuries, cancer has been one of the most devastating diseases worldwide [ 1 ]. Oral squamous cell carcinoma (OSCC) is associated with high morbidity, high malignancy, and poor prognosis, and has been one of the top 15 most prevalent cancers worldwide [ 2 , 3 ]. However, the current main treatment methods for OSCC (e.g., surgery, chemotherapy, radiotherapy, and combination therapy) have some disadvantages [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC), which mostly happens in the tissues of the tongues or lips, is one of the most common oral malignancies. 1,2 Nowadays, surgical resection is the primary therapeutic strategy for OSCC. 3,4 However, surgery is highly dependent on the medical diagnosis and lesion size, and this aggressively invasive treatment has inevitable sequelae, resulting in facial deformities and severe oral physiological dysfunction such as impaired linguistic and food-intake capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC), which mostly happens in the tissues of the tongues or lips, is one of the most common oral malignancies. , Nowadays, surgical resection is the primary therapeutic strategy for OSCC. , However, surgery is highly dependent on the medical diagnosis and lesion size, and this aggressively invasive treatment has inevitable sequelae, resulting in facial deformities and severe oral physiological dysfunction such as impaired linguistic and food-intake capabilities. , Therefore, some noninvasive treatments such as radiotherapy, photothermal therapy, and sonodynamic therapy have emerged in the therapeutic strategies of oral cancer. Radiotherapy is the primary noninvasive treatment in clinics for OSCC with less impact on the appearance and oral function, which relies on the mechanism of reactive oxygen species (ROS) generation from water radiolysis. Nevertheless, radiotherapy also has nonnegligible limitations. On the one hand, OSCC is a locally aggressive tumor characterized by massive tumor necrosis and local hypoxia, leading to low radiosensitivity. , On the other hand, radiation sequelae that hinder patients’ tolerance to high-dose radiotherapy are also an important factor limiting the course of radiotherapy, such as high-incidence radiation-induced oral mucositis and xerostomia (salivary gland injury) after head and neck radiotherapy. Therefore, it is of great significance to develop a highly efficient and low-toxic radiosensitization strategy for improving the therapeutic outcome and reducing the side effects during treatment.…”
Section: Introductionmentioning
confidence: 99%